Effect of an electric field on coalescence in gallium island films - Chizhik, S.P.; Dukarov, S.V.; Gladkikh, N.T.; Grigoryeva, L.K. (My University, 1990)
It was found that the external longitudinal electric field stimulates coalescence in gallium island films with different particle sizes on a poorly conducting carbon substrate, which can be considered as a manifestation of the particle mutual-charging effect. - - - - - - - - - - - - - - - Установлено, что внешнее продольное электрическое поле стимулирует процесс коалесценции в островковых пленках галлия с различным размером частиц на слабопроводящей углеродной подложке, что может рассматриваться как проявление эффекта взаимного заряжения частиц.
Keywords: Island films; size distribution; coalescence; Research Subject Categories::NATURAL SCIENCES::Physics::Condensed matter physics::Surfaces and interfaces